2022
DOI: 10.3390/ijerph192013605
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Accessibility and Breast Cancer Mortality in Europe

Abstract: Background: Breast cancer is the most common cause of death, due to malignant neoplasms in women worldwide. The nature of the symptoms associated with breast cancer depends on the stage of the disease. In this case, any cancerous changes in the initial phase of the disease can only be detected during imaging tests. Participation in mammography screening can reduce breast cancer mortality by up to 40%, if only 70% of the eligible population participates in preventive programs. The purpose of the study was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This evidence precisely explains the significant decrease in age-standardized breast cancer mortality rates and DALY rates in Western Europe. The high level of medical care in this region results in a concentration of breast cancer mortality among middle-aged and elderly populations, ultimately improving and extending the lifespan of breast cancer patients ( 11 ). In contrast, the burden of breast cancer in Eastern and Central Europe is concentrated among the middle-aged population, with a decrease in the burden among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence precisely explains the significant decrease in age-standardized breast cancer mortality rates and DALY rates in Western Europe. The high level of medical care in this region results in a concentration of breast cancer mortality among middle-aged and elderly populations, ultimately improving and extending the lifespan of breast cancer patients ( 11 ). In contrast, the burden of breast cancer in Eastern and Central Europe is concentrated among the middle-aged population, with a decrease in the burden among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer mortality is perhaps even more complex to predict than screening coverage, with several confounding socioeconomic factors involved ( 21 - 23 ). The results of the present study might be linked to the trend of mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified four clusters of breast cancer mortality. Cyprus, Greece, Luxembourg, Poland, Romania, Serbia, Slovakia, and Slovenia were included in the cluster of countries with increased mortality ( 21 ). Conversely, the countries with the greatest increase in online interest in mammography, such as France, Germany, United Kingdom, Sweden, Spain, were classified into the cluster with a high mortality decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poland belongs to the group of countries where the risk of breast cancer is high and is characterized by an upward trend [1]. The number of newly registered cases continues to increase, from 12,512 patients in 2000 to 17,647 in 2020 (Figure 1) [2].…”
Section: Epidemiologymentioning
confidence: 99%